STUDI PERKEMBANGAN AGROINDUSTRI TAHU PADA USAHA KELUARGA LESTARI DI KELURAHAN SUKAJADI KECAMATAN TALANG KELAPA KABUPATEN BANYUASIN - Gustian, Aan; Abubakar, Rafeah; Afriyatna, Sisvaberti (Societa: Jurnal Ilmu-Ilmu Agribisnis, 2017)
Study the development of tofu agroindustry at the lestari Family Business in Sukajadi Village District of Talang Kelapa Banyuasin Regency. The purpose of this study was to determine the development of at tofu agroindustry lestari Family Business and to calculating the amount of benefit at from the agroindustry out of lestari Family Business. This research was conducted in the Sukajadi Village District of TalangKelapa Banyuasin Regency in March from to May 2016. The method used is the case study method. The sampling method used is purposive sampling deliberately. Data collection method used is direct observation and interviews with respondents using the list of questions prepared before. Methods of data processing and analysis used for thefirs problem is descriptive qualitative method by using SWOT analysis . To answer the second problem using descriptive analysis with mathematical approach. The results showed that, development of agro-industry tofu at the lestari Family Business based on SWOT analysis has been used is, Strength: has a business license, short distribution channels, production equipment is complete, have a workforce that has experienced, able to produce every day. Weakness: Venture capital limited, production tofu not durable, not manage your finances well. Opportunity:The number of consumers need tofu as a snack, many consumers need tofu as a side dish, many traders that help to expand marketing, the waste from the tofu production are not dangerous and government support. Threat: Soybean uncertain, new arrivals, It's hard to get a loan.